The limits of community participation: examining the roles of discourse, institutions, and agency in the promotion of community participation in Thailand - Pitidol, T (2013)
This thesis is a study of how community participation is understood, enacted, produced and governed in the context of an organization that promotes community participation. The contribution of this thesis is to shed light on the frequently found gap between the expectations and the reality of community participation. In examining how community participation is promoted, the thesis focuses in particular on actors such as community leaders and development workers, and the interactions between them. The thesis applies a multi-disciplinary theoretical framework, which is built through combining theoretical approaches that include discourse analysis, institutional analysis, and the actor-oriented approach. The framework accommodates the examination of the roles of various types of social factors in shaping the workings of community participation. These include the idea of community, social relations in communities, and the agency of actors who are promoting the approach. This thesis conducts a case study of the Council of Community Organisations (CCO) programme in Thailand, which is a large-scale promotion of community participation in development and governance. The case study examines the operation of the programme from national to local level, and explores several localities where the programme is being implemented. The exploration of the CCO programme illuminates pathways through which the approach’s inner mechanisms can constrain it from fulfilling the expectations. The thesis identifies how the idea of community, through its association with the sense of collective identity, tends to distort community participation from achieving empowerment. Moreover, the social relations in communities, generally characterised by inequality and diversity of interests, frequently constrain the approach from achieving effective mobilisation of collective action. Such a constraint is often accentuated by adverse incentives that community leaders face when they become part of development interventions. Finally, it is found that the deficiencies of community participation are likely to persist. This is because the actors who are promoting the approach usually manoeuvre to gain advantages from their roles in ways that reinforce the influence of the aforementioned factors.